Seasonal monitoring of Glossina species occurrence, infection rates, and Trypanosoma species infections in pigs in West Nile Region, Uganda - Maxamhud, S.; Lindahl, Johanna F.; Mugenyi, A.; Echodu, R.; Waiswa, C.; Roesel, Kristina (Mary Ann Liebert Inc, 2022)
Introduction: Trypanosomiasis is a parasitic infection caused by the protozoa Trypanosoma. It is exclusively associated with Glossina species habitats and, therefore, restricted to specific geographical settings. It affects a wide range of hosts, including humans. Animals may carry different Trypanosoma spp. while being asymptomatic. They are, therefore, potentially important in unpremeditated disease transmission.